Strategi Peningkatan Kinerja Pemerintah Kota Batam: Peningkatan Kesadaran Masyarakat Untuk Membayar Pajak Bumi Dan Bangunan - Rendi Hairudin; Etika Khairina (UNIVED PRESS, Universitas Dehasen Bengkulu, 2023)
Tax is a mandatory assessment imposed on the people for the benefit of the state. Taxes serve as a tool to fund government expenditures, such as building projects and civil servant salaries. The purpose of this research is to show the barriers that prevent individuals from paying their taxes and uncover the tactics that the Batam City government uses to increase taxpayer awareness. Qualitative descriptive method was adopted in this investigation. Interviews and observations are used as data collection techniques. Researchers used a triangulation technique, a multi-method approach to data collection and analysis. The findings of this study indicate that Batam City's tax collection that does not reach the government's target is caused by a combination of non-compliance. by taxpayers and a complicated tax system that is difficult for the general public to understand.